Знаходження сталої часу теплової вимірювальної комірки з метою підвищення швидкодії газоаналітичних приладів - Макар, Олег; Кріль, Олександр; Кріль, Богдан (Видавництво Львівської політехніки, 2013)
In gas analysing equipment heat detectors are widely used for converting thermal physical and mechanical parameters of the gaseous mixture into an electrical signal. Heated by electric current these detectors sense thermal conductivity, heat capacity and project gasous mixture expenditure. Sensitivity and performance velocity are among the main parameters of these detectors determining the irmetrological characteristics. The given paper provides the equation of time constant of the heat measuring cell, common in gas analysing equipment, for the purpose of studying the influence of detectors’ mode changes on the performence velocity of gas analysing equipment.
Keywords: теплова вимірювальна комірка; тепловий чутливий елемент; газовий аналіз; стала часу